Pemberdayaan Masyarakat Melalui Pengelolaan Homestay di Desa Wisata - Santi, Fitta Ummaya; Tristanti, Tristanti (Journal of Nonformal Education and Community Empowerment, 2021)
The objectives of this study are to describe the problems of the community in the management of homestays, and knowing the community empowerment effortsthat can be done in developing homestays in Bejiharjo tourism village. This actionresearch was carried out on 20 homestay groups. This action research was carriedout using the model of diagnosis, planning, action implementation, andevaluation. Data and information were collected by interview technique, FGD,observation and documentation. The results of this study indicate that theproblems that exist in homestay management include internal and externalproblems. Internal includes: lack of knowledge from homestay owners regardinghomestay management, homestay services and facilities that are still limited; andpromotions that have not been maximized. Externals includ: the absence ofhomestay groups in Gelaran II Bejiharjo, problems or complaints originatingfrom visitors, as well as the number of visitors staying at homestays every month.Empowerment efforts in homestay development are carried out through homestaymanagement training and sustainable tourism, the establishment of WiraHomestay organization, increasing homestay marketing through media websites,facebook, IG.